2008
DOI: 10.1007/s00436-008-1162-6
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscopic studies on egg surface morphology and morphometrics of Culex tritaeniorhynchus and Culex quinquefasciatus (Diptera: Culicidae)

Abstract: Culex tritaeniorhynchus Giles, 1901 and Culex quinquefasciatus Say, 1823 is an important vector of Japanese encephalitis and Bancroftian filariasis, respectively in India and South East Asian countries. In this paper, we are describing the surface morphology and morphometrics of the egg of C. tritaeniorhynchus in comparison with C. quinquefasciatus for the first time. The results indicated that eggs of both the species appears to be similar to great extent in surface morphology, however, morphometrics provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 5 publications
1
24
0
Order By: Relevance
“…The average life period of a mosquito is about 21 days and undergoes three gonotrophic cycle (WHO, 2006). Human infections are mainly transmitted by Culex tritaeniorrhynchus Giles, which is the principal vector of JE in India and South East Asian countries (Suman et al, 2008). The female specimens are infective 9-10 days after having taken the viraemic blood meal, having undergone three gonotropic cycles (Gajanana et al, 1997).…”
Section: Enzootic Cycle Of Jevmentioning
confidence: 99%
“…The average life period of a mosquito is about 21 days and undergoes three gonotrophic cycle (WHO, 2006). Human infections are mainly transmitted by Culex tritaeniorrhynchus Giles, which is the principal vector of JE in India and South East Asian countries (Suman et al, 2008). The female specimens are infective 9-10 days after having taken the viraemic blood meal, having undergone three gonotropic cycles (Gajanana et al, 1997).…”
Section: Enzootic Cycle Of Jevmentioning
confidence: 99%
“…There are species‐specific micropatterns formed on the surface of mosquito eggs (Hinton ; Sahlen ; Suman et al . ). Female mosquitoes produce the eggs, but the chorion is deposited before the eggs are fertilized.…”
Section: Introductionmentioning
confidence: 97%
“…; Suman et al . , ). Such studies revealed that the chorionic ultrastructures such as micropyle and polygonal patterns can be used as strong taxonomic characters for differentiating between mosquito eggs (Suman et al .…”
Section: Introductionmentioning
confidence: 99%
“…Culex tritaeniorhynchus Giles is an important vector of JE in India and South East Asian countries (Suman et al 2008). JE is endemic in few states of India and highly endemic in few districts of Tamil Nadu, Southern India (Reuben and Gajanana 1997;Sarkari et al 1984;Ravi et al 1989).…”
Section: Introductionmentioning
confidence: 99%